Impact of various heat treatment processes and welding speeds on the mechanical properties and microstructures of soft/hard composite joints - Yu, Yang; Wang, Zhao; Chen, Biao; Zhang, Shuchao; Du, Jinliang (Frontiers in Materials, 2024)
There is a certain contradiction between the formability and strength of auto parts. In this work, the whole-process processing technology of hot stamping soft steel was designed, and 500MPa grade mild steel (500HS) with uniform microstructure was prepared. To take into account the strength and formability of hot stamping soft steel, here, based on laser welding technology, 500MPa grade soft steel, and 1500MPa grade hard steel are benignly composited, and by adjusting the laser welding speed and heat treatment process, the loss of mechanical properties caused by the weld seam is eliminated. A soft/hard composite steel for automobiles with excellent strength, ductility and formability is obtained. To maintain excellent deformation resistance and bonding force of the weld, the heat-affected zone of 500HS retains part of bainite and pearlite, which is beneficial to the strain compatibility and stress partitioning with the microstructure of the base metal, and the hardness is low. After heat treatment, which helps to transfer the stress concentration effect to the 500HS base metal with strong energy absorption capacity, so that the clad steel has excellent comprehensive mechanical properties. This process is developed based on existing industrialized equipment and has broad application prospects.